1986
DOI: 10.1055/s-2007-1003577
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activators (Urokinase) Mediate Neovascularization: Possible Role in Tumor Angiogenesis

Abstract: Most malignant solid tumors induce the growth of new capillaries from the vascular bed by tumor angiogenesis, and dormant tumors can grow only if new capillaries are induced and penetrate into the tumor. 2 Since many human tumors produce a plasminogen activator (PA) immunochemically and biochemically identical to urokinase (the PA produced by the kidney and excreted in urine), highly purified preparations of both high and low M r urokinase have been examined for their potential to mediate neovascularization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In addition, tumor cells induce neovascularization in vivo [36], and increased vascularity is one of the characteristic features of glioblastomas. During the formation of new blood vessels, endothelial cells degrade basement membrane and ECM and migrate into surrounding tissues, a process that is thought to be facilitated by increased production of proteolytic enzymes from the endothelial cells [37]. In our immunohistochemical studies it was shown that MMP-2 is localized within endothelial cells of blood vessels of malignant astrocytomas, suggesting a role for MMPs in angiogenesis of brain tumors.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, tumor cells induce neovascularization in vivo [36], and increased vascularity is one of the characteristic features of glioblastomas. During the formation of new blood vessels, endothelial cells degrade basement membrane and ECM and migrate into surrounding tissues, a process that is thought to be facilitated by increased production of proteolytic enzymes from the endothelial cells [37]. In our immunohistochemical studies it was shown that MMP-2 is localized within endothelial cells of blood vessels of malignant astrocytomas, suggesting a role for MMPs in angiogenesis of brain tumors.…”
Section: Discussionmentioning
confidence: 54%
“…It is also noticed that molecular events associated with those that take place during tumor invasion including growth control, regulation of motility and matrix degradation by proteolytic enzymes [43]. Several experimental observations suggest that MMPs are not only breaking down the physical barrier of extracellular matrix but also modulating the growth factors and cytokines stored in the extracellular matrix which may promote the neoplastic progression [44].…”
Section: Discussionmentioning
confidence: 99%
“…Upon ligand binding (such as pro-uPA, uPA or ATF), uPAR undergoes either a conformational change or Introduction 10 demonstrated to play a role in endothelial cell migration and differentiation. uPA itself had a proangiogenic effect, when assayed in the rabbit cornea or on chicken chorioallantoic membrane (Berman et al, 1982;Goldfarb et al, 1986;Rabatti et al, 1999). Studies in PAI-1 null mice have revealed an absolute requirement for PAI-1 in tumor-induced angiogenesis.…”
Section: Non-proteolytic Functions Of the Upa Systemmentioning
confidence: 99%